Modeling and Investigation of the Reduction Zone in A Downdraft Biomass Gasifier. Issue 1 (1st April 2022) - Zhou, Junjie; Han, Kui; Tang, Songzhen; Tao, Wu; Fu, Weidong
Abstract: The fixed bed gasifier has simple structure, convenient operation and maintenance, and is suitable for use in rural areas. In this paper, a downdraft fixed bed gasifier was designed for biomass gasification using corn cob as raw material. COMSOL Multiphysics software was used to simulate the reduction zone of biomass gasifier. The temperature field and concentration distribution of the reduction zone were studied. The influence of structural parameters of the reduction zone on the composition of syngas was analyzed. The rates of major chemical reactions in the reduction zone were also compared in detail.